2021
DOI: 10.1183/23120541.00143-2021
|View full text |Cite
|
Sign up to set email alerts
|

Biologicals in childhood severe asthma: the European PERMEABLE survey on thestatus quo

Abstract: IntroductionSevere asthma is a rare disease in children, for which three biologicals –anti-IgE, anti-IL-5 and anti-IL-4RA antibodies– are available in European countries. While global guidelines exist on who should receive biologicals, knowledge is lacking on how those guidelines are implemented in real life and which unmet needs exist in the field. In this survey, we aimed to investigate the status quo and identify open questions in biological therapy of childhood asthma across Europe.MethodsStructured interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Nevertheless, a review dedicated to these new trends showed that the adolescents’ adherence to inhalers recorded by electronic monitoring was at less than 50% [ 43 ], even if recent experiences with electronic reminders are showing encouraging results from this point of view [ 44 , 45 ]. However, although previous studies investigating these interventions, aiming to promote adherence in adolescents with asthma, proved to be of limited effectiveness [ 46 , 47 , 48 ], additional studies oriented to better understanding and possibly removing the deeper reasons for such poor attitudes in adolescents regarding maintaining long-term asthma strategies are still needed, even in the case of mild asthma [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a review dedicated to these new trends showed that the adolescents’ adherence to inhalers recorded by electronic monitoring was at less than 50% [ 43 ], even if recent experiences with electronic reminders are showing encouraging results from this point of view [ 44 , 45 ]. However, although previous studies investigating these interventions, aiming to promote adherence in adolescents with asthma, proved to be of limited effectiveness [ 46 , 47 , 48 ], additional studies oriented to better understanding and possibly removing the deeper reasons for such poor attitudes in adolescents regarding maintaining long-term asthma strategies are still needed, even in the case of mild asthma [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of pediatric patients can achieve good asthma control. However, a minority will have severe asthma even after optimal therapy [ 6 , 17 ]. Initially, inhaled corticosteroids (ICS) brought immense relief from clinical symptoms and lung function indexes [ 6 ].…”
Section: Approved Biologic Agentsmentioning
confidence: 99%
“…There are currently five mAb therapies available for children with severe asthma younger than 18. Not long ago, only omalizumab had approval, originally in the United States since 2003 and subsequently in Europe in 2005, but recently, the European Medicines Agency (EMA) approved mepolizumab and benralizumab, in 2015 and 2017, respectively, dupilumab in 2019 for children [ 2 , 17 , 19 ], and tezepelumab first in the USA in December 2021 and at the Global Initiative for Asthma (GINA) in 2022 [ 6 , 20 ]. The main characteristics of each of the immunomodulatory mAbs approved for pediatric severe asthma have been reported in Table 1 .…”
Section: Approved Biologic Agentsmentioning
confidence: 99%
“…Trials tend to use Minimal Clinical Important Difference (MCID) or Minimal Important Difference (MID) to define treatment response where available, prioritising reproducibility and distinguishing treatment from placebo participant cohorts. National healthcare regulators across Europe use a range of outcome criteria to determine treatment access and reimbursement policies [2,3]. Over the last 20 years, measures of health related quality of life (QoL) were not included as clinical trial endpoints in over one third (37%) of randomised controlled trials (RCTs) of severe asthma treatments, despite a majority of patients considering improved quality of life as the most important outcome for biological therapy [4,5].…”
Section: Introductionmentioning
confidence: 99%